2018
DOI: 10.1016/j.neuroscience.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Early-blind Individuals Show Impaired Performance in Wine Odor Categorization

Abstract: Blind individuals display superior sensory abilities in other modalities, yet results remain contradictory regarding their performance on olfactory tasks. Using complex ecological olfactory tasks, we evaluated the impact of blindness on olfactory performance. We tested 12 early-blind individuals (M = 49, SD = 13.09) and 12 sighted controls (M = 49, SD = 14.31) who were all blindfolded. Based solely on the wine odors, participants evaluated 24 pairs of wine and determined if both samples belonged to the same ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although this may lead one to conclude the olfactory function is unchanged in blind individuals, the picture may be more complex, notably if the tasks themselves present a higher level of difficulty, a phenomenon that was previously shown in blind individuals within other modalities (Alary et al, 2008; Simon et al, 2002). More specifically, during a wine odour categorization task (Manescu et al, 2018), early‐blind individuals presented lower scores compared with sighted controls, suggesting the importance of previous visual experiences in the formation of internal representations of complex odours, such as wines. On the other hand, congenitally blind individuals outperformed controls in an odour localization task but not in identification tasks (Manescu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although this may lead one to conclude the olfactory function is unchanged in blind individuals, the picture may be more complex, notably if the tasks themselves present a higher level of difficulty, a phenomenon that was previously shown in blind individuals within other modalities (Alary et al, 2008; Simon et al, 2002). More specifically, during a wine odour categorization task (Manescu et al, 2018), early‐blind individuals presented lower scores compared with sighted controls, suggesting the importance of previous visual experiences in the formation of internal representations of complex odours, such as wines. On the other hand, congenitally blind individuals outperformed controls in an odour localization task but not in identification tasks (Manescu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the scientific evidence backing the olfactory compensation hypothesis in the context of odor identification is rather weak; cued odor identification tests rather do not report blind people's superior performance, and the evidence for free odor identification is mixed (see Sorokowska, Sorokowski, Karwowski, Larsson, & Hummel, 2019 for a review and meta‐analysis). An interesting, recent study on wine odor perception additionally showed no superiority of early blind people in olfactory differentiation and classification, and even impaired wine odor categorization skills in the blind as compared with the sighted people (Manescu et al, 2018). Still, identification abilities in blind and sighted people may vary greatly for different, individual odorants (Murphy & Cain, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…This is presumably because the subtle gradations of colour in wine have more meaning, and hence set more specific flavour expectations, for experts than for the beginners (i.e., the novice, or social wine drinkers). After all, the latter may only really meaningfully discriminate between broad categories including red, white, rosé, and, these days, possibly also orange wines (see also Manescu et al, 2018). 1 There is a much richer range of colours in the world of wine than is the case for perhaps any other class of beverage (see Spence, 2010b).…”
Section: Introductionmentioning
confidence: 99%